Effect of modeling liquid application on color stability and surface roughness of single-shade composites - Melek Güven Bekdaş; Ihsan Hubbezoglu (BMC Oral Health)
Abstract Objectives The objective of this study was to examine the effects of modeling liquid application on the color stability and surface roughness of single-shade composites. Materials and methods Single-shade composites were divided into 4 main groups according to their contents. A total of 64 disc-shaped samples (8 × 2 mm) were prepared, 16 in each group, by using Teflon molds. The samples were divided into two subgroups on the basis of the application of a modeling liquid. After the initial color and roughness measurements, the samples were immersed in coffee for 12 days. Color changes were assessed via a spectrophotometer and ΔE values were calculated via the CIELAB formula. The surface roughness (Ra) was measured via a profilometer. The data were subjected to statistical analysis via two-way analysis of variance and Tukey’s test to examine pairwise differences at a significance level of 0.05. Results The application of modeling liquid reduced discoloration in Charisma Diamond One (CDO) and Vittra APS Unique (VUA), whereas it slightly increased discoloration in Omnichroma (OMN) and Zenchroma (ZNC). However, only the changes in CDO were statistically significant (p < 0.05). Among the composite control groups baseline and after the coloring procedures, the highest surface roughness degree was observed in the CDO group, while the lowest surface roughness degree was observed in the OMN and ZNC groups (p < 0.05), and the differences between them were found to be significant (p > 0.05). The surface roughness and color changes approached the mean values in the subgroups where the modeling liquid was applied, and there was no significant difference between them (p > 0.05). The application of modeling liquid was observed to reduce the variation in initial roughness among the composites, bringing their roughness values closer to an average range (0.26–0.34). Conclusion Modeling liquid application increased roughness and discoloration in composites with initially low surface roughness (OMN and ZNC) while reducing roughness and discoloration in composites with initially high surface roughness (VUA and CDO). Clinical relevance Modeling liquid application should be approached more cautiously in composites with high polishability, despite contributing to clinical use in composites with high roughness values.